2011
DOI: 10.1039/c1cp22185j
|View full text |Cite
|
Sign up to set email alerts
|

Heat capacity and glass transition in P2O5–H2O solutions: support for Mishima's conjecture on solvent water at low temperature

Abstract: The P(2)O(5)-water system has the widest range of continuously glass-forming compositions known for any glassformer + water binary system. Despite the great range of structures explored by the glasses and liquids in this system, the glass transition temperature (T(g)) itself varies in a simple monotonic fashion. However the values of T(g) reported in the literature show wide disagreement, linked to the different methods of measurement employed. In this work we use differential scanning calorimetry (DSC) to obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
2
36
1
Order By: Relevance
“…(5) into 94 and more recently Corti et al 95 found a value of 35 J K −1 mol −1 for c l 1 − c g 1 from binary aqueous solutions containing hydrazine (N 2 H 4 ), hydrogen peroxide (H 2 O 2 ), and phosphorus pentoxide (P 2 O 5 ), respectively. These discrepancies are explained in terms of a "fragile-to-strong" liquid transition of very dilute solutions which is experimentally inaccessible due to homogeneous ice freezing.…”
Section: B Multi-component Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…(5) into 94 and more recently Corti et al 95 found a value of 35 J K −1 mol −1 for c l 1 − c g 1 from binary aqueous solutions containing hydrazine (N 2 H 4 ), hydrogen peroxide (H 2 O 2 ), and phosphorus pentoxide (P 2 O 5 ), respectively. These discrepancies are explained in terms of a "fragile-to-strong" liquid transition of very dilute solutions which is experimentally inaccessible due to homogeneous ice freezing.…”
Section: B Multi-component Systemsmentioning
confidence: 98%
“…These discrepancies are explained in terms of a "fragile-to-strong" liquid transition of very dilute solutions which is experimentally inaccessible due to homogeneous ice freezing. 82,95 This transition and hence the c l 1 − c g 1 which should be used in Eq. (6) depend on the solute.…”
Section: B Multi-component Systemsmentioning
confidence: 99%
“…The T g of P 2 O 5 has been measured to be between 590 K 33 and 665 K 34 by (10) and experimental data. Data for x > 0.5 were determined by DSC 93 and for x = 0.5 by dilatometer. 32 The largest discrepancy between the experimentally determined and the modeled T g values is 4 K. The dotted line is for a topological model taking the DBO as a network forming atom with one constraint for the P-DBO bond and two additional α constraints for each Q n .…”
Section: Polyphosphoric Acidsmentioning
confidence: 99%
“…55,56 We suggest here that something similar occurs in polyol aqueous solutions, and hence the volumetric properties of water are different from that of bulk water (as represented by the linear temperature dependence shown in Figure 2). …”
Section: Volumetric Properties Of the Pure Componentsmentioning
confidence: 79%